PENGARUH INDEPENDENSI, KOMPETENSI, DAN RUANG LINGKUP PEKERJAAN AUDIT PENGAWAS PADA EFEKTIVITAS PENGENDALIAN INTERN KOPERASI DI KABUPATEN BULELENG - Putra, Bayu Sadhana; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2014)
The purpose of this study was to determine the effect of independence, competence, and the scope of audit work supervisor of the effectiveness of internal control of the cooperative. This research was conducted in co-operatives located in Buleleng regency. The number of samples taken 42 samples cooperative, with purposive sampling method. Analysis technique used is multiple linear regression. The results of the analysis found that the independence, competence, and the scope of audit work supervisors have a significant effect on the effectiveness of internal control co-operative, which means fluctuations independence, competence, and the scope of audit work supervisor will have an impact on the effectiveness of internal control changes cooperatives.
Keywords: Supervisor, Internal Control Effectiveness, Independence, Competency, Scope of Work of the Audit.